Malignant peripheral nerve sheath tumour in an unusual location of the urinary bladder: case report and review of literature (2021)
Background: Malignant peripheral nerve sheath tumour (MPNST) is a rare malignant soft tissue neoplasm of ectomesenchymal origin. They usually arise from a major or minor peripheral nerve branch or its sheath and also from somatic soft tissues. The most common sites of origin include the extremities and trunk but can sometimes arise an unusual site resulting in the demise of the patient before any intervention. Case presentation: We report a case of 58-year-old male who presented with complaints of weight loss of a year duration, abdominal swelling of 10 months duration and easy fatigability of 3 weeks duration. Digital rectal examina tion revealed a huge frm mass 6 cm from the anal verge which was non-tender. Abdomino-pelvic ultrasound scan revealed an irregular heterogeneous mass in the posterior wall of the urinary bladder measuring 15.1cmx 14.0 cm with bilateral dilatation of the renal pelvi-calyceal system and ureters. His clinical condition continued to deteriorate while on hospital admission, and he died on the12th day of admission. Post-mortem examination showed a rough ovoid tumour mass frmly adherent to the posterior wall of the bladder with compression of both ureters. Histological and immunohistochemical analysis of the tumour revealed the diagnosis of a MPNST. The fnal anatomical diagnosis and cause of death was that of a malignant peripheral nerve sheath tumour of the urinary bladder with obstructive uropathy and severe sepsis. Conclusion: MPNST can arise at unusual sites other than its common location in the extremities and the existence of neurofbromatosis may not be present. High index of suspicion of MPNST should be raised in rapidly growing painless tumour in and around a nerve tissue. Prompt radio-imaging with biopsy and expert immunohistochemical analysis of lesions will lead to early diagnosis and intervention. Molecular targeted therapies following surgery for MPNST should be developed to improve prognosis and patient outcomes.